The Implementation of Decision Aids During Medical Consultations for Lung Cancer Patients: A Focus Group Within I3LUNG Project - Valeria Sebri; Patrizia Dorangricchia; Dario Monzani; Chiara Marzorati; Roberto Grasso; Lorenzo Conti; Giuseppe Lo Russo; Leonardo Provenzano; Andra Diana Dumitrascu; Gabriella Pravettoni (2025)
Abstract Lung cancer patients generally receive several information regarding their illness characteristics and available intervention. Therefore, patients can experience confusion, leading to anxiety and distress that might damage the relationship with physicians and treatment adherence. Literature showed that implementing decision aid tools during consultation can promote patients’ knowledge and awareness about lung cancer and available oncological intervention, improving a shared decision-making process. However, not all lung cancer patients always appreciate decision aids’ implementation. The present qualitative study explored patients’ opinions and preferences regarding the implementation of decision aids during medical consultation. Twenty-two lung cancer patients who have already attended medical consultations for lung cancer voluntarily participated in four online focus groups carried out between January 2023 and December 2024. A thematic analysis with a bottom-up approach highlighted three main themes: the typology and number of information that patients would have received, the relevance of patient-and-doctor relationship, and the effects of providing additional decision-making tools on patients’ emotions and preferences. Findings showed controversial opinions among patients, highlighting the relevance of personalized intervention tailored to patients’ preferences. Practical implications are given.